Etika Akademik dalam Tradisi Ilmiah di Kalangan Akademisi IAIN Ar-raniry - Abdul Wahid (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2012)
IAIN Ar-Raniry is an educational institute that carries on both knowledge and Islamic missions. Both aspects are gauge to measure the development of knowledge performed by the institute. Islamic scholar ethic is another measurement for academic commitment on religious values. For that, the development of knowledge at the institute can be gauged from the productivity of the academic, a side of the quality. While the commitment to preserve and to implement the Islamic ethics, can be witness from the originality of their works. To the best of writer‟s observation, the level of productivity seems relatively under expectation, while the ethic on the other hand, is seemingly preserved by academic of the Institute.